A fluid‐driven earthquake swarm on the margin of the Yellowstone caldera. Issue 9 (16th September 2013) - Shelly, David R.; Hill, David P.; Massin, Frédérick; Farrell, Jamie; Smith, Robert B.; Taira, Taka'aki
Abstract: [1] Over the past several decades, the Yellowstone caldera has experienced frequent earthquake swarms and repeated cycles of uplift and subsidence, reflecting dynamic volcanic and tectonic processes. Here we examine the detailed spatial‐temporal evolution of the 2010 Madison Plateau swarm, which occurred near the northwest boundary of the Yellowstone caldera. To fully explore the evolution of the swarm, we integrated procedures for seismic waveform‐based earthquake detection with precise double‐difference relative relocation. Using cross correlation of continuous seismic data and waveform templates constructed from cataloged events, we detected and precisely located 8710 earthquakes during the 3 week swarm, nearly 4 times the number of events included in the standard catalog. This high‐resolution analysis reveals distinct migration of earthquake activity over the course of the swarm. The swarm initiated abruptly on 17 January 2010 at about 10 km depth and expanded dramatically outward (both shallower and deeper) over time, primarily along a NNW striking, 55° ENE dipping structure. To explain these characteristics, we hypothesize that the swarm was triggered by the rupture of a zone of confined high‐pressure aqueous fluids into a preexisting crustal fault system, prompting release of accumulated stress. The high‐pressure fluid injection may have been accommodated by hybrid shear and dilatational failure, as is commonly observed in exhumed hydrothermally affected fault zones. This process has likely occurred repeatedly in Yellowstone as aqueous fluids exsolved from magma migrate into the brittle crust, and it may be a key element in the observed cycles of caldera uplift and subsidence. Key Points: We detect and precisely locate 4 times as many swarm earthquakes as in the catalog Pronounced swarm migration suggests triggering by diffusing pore fluid pressure Fluids exsolved from magma probably escaped from the ductile‐to‐brittle region